Enhancing Students’ Vocabulary Mastery Through Big City Adventure Game in Junior High School English Learning - Aswar Aswar; Katharina Maria Glas; Benghezla Mohamed (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to determine whether the use of the computer game Big City Adventure was effective in developing students’ vocabulary mastery, especially noun vocabulary, among eighth-grade students of Junior High School Muhammadiyah Palopo in the 2025/2026 academic year. Methodology: This study used a pre-experimental design with one-group pre-test and post-test. The population consisted of 20 eighth-grade students, and total sampling was applied. Instruments included vocabulary tests (50 noun vocabulary items), questionnaires (10 Likert-scale items), computer, LCD projector, dictionary, and the Big City Adventure computer game as learning media. Main Findings: The findings showed significant improvement in students’ vocabulary mastery after treatment. The pre-test mean score was 4.99, while the post-test mean score increased to 8.38. Most students moved from poor and fair categories to good, very good, and excellent categories. Students also gave positive responses toward learning vocabulary using the computer game. Novelty/Originality of this study: This study introduced Big City Adventure as an interactive computer game for teaching noun vocabulary in junior high school. Unlike conventional memorization methods, this approach combined visual learning, student engagement, and enjoyable gameplay, helping reduce boredom and increase motivation, interest, and vocabulary retention in English learning.